Effects of Helium and 40% O2 on graded exercise with self-contained breathing apparatus - Eves, N. D.; Petersen, S. R.; Jones, R. L. (Canadian Journal of Applied Physiology, 2003)
Maximal exercise performance is decreased when breathing from a self-contained breathing apparatus (SCBA), owing to a ventilatory limitation imposed by the increased expiratory resistance. To test the hypothesis that decreasing the density of the breathing gas would improve maximal exercise performance, we studied 15 men during four graded exercise tests with the SCBA. Participants breathed a different gas mixture during each test: normoxia (NOX; 21% O2, 79% N2), hyperoxia (HOX; 40% O2, 60% N2), normoxic helium (HE-OX; 21% O2, 79% He), and hyperoxic helium (HE-HOX; 40% O2, 60% He). Compared to NOX, power output at the ventilatory threshold and at maximal exercise significantly increased with both hyperoxic mixtures. Minute ventilation was increased at peak exercise with both helium mixtures, and maximal aerobic power (VO2max) was significantly increased by 12.9 ± 5.6%, 10.2 ± 6.3%, and 21.8 ± 5.6% with HOX, HE-OX, and HE-HOX, respectively. At peak exercise, the expired breathing resistance imposed by the SCBA was significantly decreased with both helium mixtures, and perceived respiratory distress was lower with HE-HOX. The results show that HE-OX improved maximal exercise performance by minimizing the ventilation limitation. The performance-enhancing effect of HOX may be explained by increased arterial oxygen content. Moreover, HE-HOX appeared to combine the effects of helium and hyperoxia on VO2max.